The Photojournalism of Del Hall : New Orleans and Beyond, 1950s-2000s - Campanella, Richard (Book collections on Project MUSE., 2015)
"With the aid of previously unpublished photographs and stills, critically acclaimed geographer and author Richard Campanella turns the focus around to the Emmy Award?winning photojournalist and presents the life of a quiet observer who captured critical episodes in American history. From Hall?s start in New Orleans at WWL-TV covering lunch-counter sit-ins and the integration of schools in the Ninth Ward to his lauded work for CBS News, filming Walter Cronkite, 60 Minutes, and Charles Kuralt, Campanella commemorates Hall?s remarkable contributions to journalism as the field expanded from print to television. This visually captivating and lively biography follows Hall as he is chased by the Ku Klux Klan, shot at by the Viet Cong, journeys to Moscow to cover President Nixon?s historic visit, and almost dies in a helicopter crash at the America?s Cup race. Campanella traces the life of a tireless documentarian and pioneer who not only photographed history as it happened, but also filmed one of the first full-color TV documentaries and redefined nonlinear computerized editing" --from the publisher.